SME finance in Europe: introduction and overview - Rien Wagenvoort (EIB Papers, 2003)
Introducing the topic of SME finance and summarising the main findings of the contributions to this edition of the EIB Papers, this overview stresses the importance of relationship banking for the supply of SME credit; points out the differences and similarities in the capital structure of firms across size classes and across Europe; observes that while there is little evidence of widespread SME credit rationing, financial market imperfections may nevertheless curb SME growth; and highlights that the changes in Europe's financial landscape - including bank consolidation and Basel II - promise to foster SME finance.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; EU-Staaten